TRANSDERMAL DRUG DELIVERY AS A NEW AND SAFE DIRECTION OF DRUG DELIVERY - Osmałek, Tomasz; Ravliv, Yulia; Hroshovyi, Тaras (Collection of scientific papers «ΛΌГOΣ», 2022)
An unprecedented attack by Russian troops on Ukraine destroyed the world order. War always brings death and destruction. Due to the ongoing hostilities in Ukraine, many have changed their conditions and lifestyle, nutrition, the ability to follow the rules of personal hygiene, psycho-emotional state, and more. During this period, there was a significant increase in fungal diseases. Forced stay in bomb shelters, basements, and places of mass accumulation hurts health and contributes to the development of mycoses of the feet and fungal damage to the nail plates [1].